2021
DOI: 10.1016/j.amepre.2021.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Detailing to Promote HIV Pre- and Postexposure Prophylaxis Among Women's Healthcare Providers in New York City

Abstract: Introduction:Equitable access to HIV pre-and postexposure prophylaxis for women is essential to ending the HIV epidemic. Providers' lack of knowledge and comfort in discussing and prescribing pre-exposure prophylaxis to women persist as barriers.Methods: From May to November 2019, the New York City Health Department conducted its first public health detailing campaigns among women's healthcare providers to promote pre-and postexposure prophylaxis and the associated best practices. Over 2 campaigns (10 weeks ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…To (Wahnich et al, 2021), a structural PrEP intervention to improve PrEP access. In this intervention, trained health department representatives introduced an "Action Kit," including U.S. Public Health Service's PrEP clinical practice guideline to 1,348 medical providers at women's health clinics in New York City.…”
Section: Normalizing Prep Carementioning
confidence: 99%
See 2 more Smart Citations
“…To (Wahnich et al, 2021), a structural PrEP intervention to improve PrEP access. In this intervention, trained health department representatives introduced an "Action Kit," including U.S. Public Health Service's PrEP clinical practice guideline to 1,348 medical providers at women's health clinics in New York City.…”
Section: Normalizing Prep Carementioning
confidence: 99%
“…Positive findings from the PrEP and PEP Public Health Detailing Campaign for Cisgender and Transgender Women (Wahnich et al, 2021) and Project SHE (Roth et al, 2021) suggest that better PrEP access may be achieved when providers, who have established trusted relationships with patients who are PrEP candidates, proceed and prescribe PrEP directly instead of referring their patients who are candidates for PrEP to HIV specialists. To expand PrEP services, the Health Resources and Services Administration (HRSA) Bureau of Primary Health Care (BPHC) is implementing the Ending the HIV Epidemic (EHE)-Primary Care HIV Prevention (PCHP) project.…”
Section: Normalizing Prep Carementioning
confidence: 99%
See 1 more Smart Citation
“…17 The 2023 USPSTF guidelines 3 point to a number of structural barriers to PrEP implementation and uptake, and novel approaches are needed to address these barriers. Clinicians may benefit from public health detailing (educational outreach from health department representatives) on available PrEP options and how to prescribe them and counsel patients 18 and from support tools such as electronic health record algorithms to identify persons at risk for HIV acquisition. 19 Additionally, shifting tasks from physicians to PrEP navigators or nurses could increase efficiencies and help expand PrEP access.…”
mentioning
confidence: 99%
“…The paradox in PrEP prescription patterns suggests that HIV specialists are the most informed and experienced in prescribing antiretroviral treatment (ART) and PrEP, but primary care providers and others, such as obstetricians/gynecologists and emergency medicine providers, are the specialists who are more likely to encounter the HIV-negative individuals who would benefit from PrEP [10,11]. PrEP guidelines, conferences, webinars, training modules, and public health detailing have improved HIV specialists’ and primary care providers’ knowledge of and willingness to prescribed PrEP [12,13]. Studies have shown that the number of HIV specialists and primary care providers who prescribe PrEP in the United States has risen steadily but remains insufficient [14,15].…”
mentioning
confidence: 99%